Indonesia's Pro-People Foreign Policy in Handling Indonesian Seafarers on Chinese Vessels - Chynda Izzati (PT Publikasiku Academic Solution, 2025)
Indonesia sends a large number of its seafarers to work on foreign fishing vessels, mainly because the pay is better than what they can earn at home, but unfortunately, many of them end up facing tough conditions, abuse, and little protection. This happens largely because the system meant to protect them is full of gaps, there are unclear recruitment rules, different government agencies stepping on each other’s toes, and no central database to keep track of who’s working on which vessel. A striking example is the case of Indonesian crew members on the Chinese vessel Long Xing 629, which caught global attention after one of the crew died and was buried at sea, raising serious concerns about how these workers are treated. This article looks at how the Indonesian government reacted, using a pro-people foreign policy approach to push for accountability and better protection of its citizens. While it’s clear that the government is starting to take these issues more seriously, there’s still a long way to go in fixing the system so Indonesian seafarers are truly safe and supported.